Sports Participation and Health Care Costs in Older Adults Aged 50 Years or Older - Codogno, Jamile S. [UNESP]; Monteiro, Henrique L. [UNESP]; Turi-Lynch, Bruna C.; Fernandes, Romulo A. [UNESP]; Pokhrel, Subhash; Anokye, Nana (Human Kinetics Publ Inc, 2020)
The objective of the study was to analyze the relationship between sports participation and health care costs in older adults. The sample was composed of 556 participants (145 men and 411 women) who were followed from 2010 to 2014. The engagement in sports considered three different components (intensity, volume, and previous time). Health care costs were assessed annually through medical records. Structural equation modeling (longitudinal relationship between sport and costs) and analysis of variance for repeated measures (comparisons over time) were used. Health care costs increased significantly from 2010 to 2014 (analysis of variance; p value = .001). Higher baseline scores for intensity were related to lower health care costs (r= -.223, 95% confidence interval [-.404, -.042]). Similar results were found to volume (r = -.216, 95% confidence interval [-.396, -.036]) and time of engagement (r= -.218, 95% confidence interval [-.402, -.034]). In conclusion, higher sports participation is related to lower health care costs in older adults.
Keywords: health costs; health services; healthy lifestyle; sports medicine